Comparing Drone and Vessel‐Based Imaging to Quantify Epibiont Coverage on Humpback Whales - Isabel A. R. Taylor; Ticiana Fettermann; Barry McGovern; David S. Schoeman; Adrian B. McCallum; Stephanie H. Stack (Marine Mammal Science, 2026)
Cetacean epibionts offer noninvasive insights into host health, physiology, and spatial ecology, yet quantitative assessments in wild populations remain scarce. Although vessel‐based observations may be limited by field of view and analyst input, unoccupied aerial vehicles (UAVs; drones) are increasingly used to monitor cetacean health indices, enhancing observational availability and reproducibility. However, the suitability of drones for quantifying epibiota has not been thoroughly evaluated. Implementing a standardized workflow, we compared dorsal proportional epibiont coverage estimates derived from drone‐based imagery and traditional vessel‐based techniques across reproductive classes of humpback whales ( Megaptera novaeangliae ). We analyzed 32 paired datasets using pixel‐based methods, incorporating semiautomated graph‐cut segmentation and iterative color‐thresholding. Drone‐derived estimates of epibiont coverage consistently exceeded vessel‐based measures, which averaged 58% of the relative coverage estimated from corresponding drone imagery, partly attributable to variable lighting during image capture. Nevertheless, 94% of paired observations differed by less than 5% in absolute coverage, indicating strong agreement. While refinement of flight parameters, image resolution, and further validation are recommended, we demonstrate that drones can provide a reliable source of quantitative epibiont data, with potential applicability across diverse epibiont–host systems, benefiting cetacean population health monitoring programs and informing conservation strategies, particularly for elusive or understudied species.